Monitoring mission for multi-drones using decentralized chaos-bidding consensus with backstepping control via lyapunov barrier functions - Muhammad Zakiyullah Romdlony; Rashad Abul Khayr; Yul Yunazwin Nazaruddin; Tua Agustinus Tamba; Md. Abdus Samad Kamal (Universitas Negeri Padang, 2025)
The mobility and flexibility of a quadrotor make it a popular choice for monitoring missions in remote areas. However, remote environments introduce constraints due to limited charging and communication stations that must be considered, alongside the possibility of collision with the environment. To ensure the quadrotor task was completed, a decentralized chaos-bidding consensus for decentralized task allocation was proposed, accompanied by control, Lyapunov, and barrier functions. These functions were simplified using the backstepping method to ensure the quadrotor's safety during task execution. The proposed method was evaluated through numerical simulation in multiple situations. The results indicate a minimum of 3% reduction in task completion time compared to other methods. When the battery constraint was applied, the proposed method successfully directed the drone to return to base before battery depletion and reassigned the task to other available quadrotors, thereby reducing the overall completion time for the entire system. Furthermore, this framework demonstrates the potential to support long-duration missions where continuous operation is required without relying heavily on ground control. The decentralized nature of the system also increases scalability, allowing multiple quadrotors to cooperate efficiently under dynamic environmental conditions. These advantages highlight the relevance of the proposed control strategy for practical field deployment, particularly in inaccessible locations.